Endometrioid Carcinoma with Hepatoid Differentiation: A Case Report and Comparison to Literature. (28th October 2020) - Bowers, K A; Johannesen, E; Nguyen, V
Abstract: Introduction/Objective: High-risk endometrial carcinomas comprise only 15% of all uterine malignancies but are responsible for over 50% of deaths. Hepatoid malignancies of the endometrium (HME) are rare entities with a distinct morphology that is important to recognize because it is associated with rapid progression and high mortality. Methods: We report a case of a HME and compare it to a collective review of 17 HME cases from the literature. Results: A 61-year old female presented with post-menopausal bleeding and was diagnosed with endometrioid carcinoma with hepatoid differentiation. The hepatoid component was strongly positive for hepatocyte specific antigen (HepPar-1/OCH1E5). The entire tumor was negative for alpha-fetoprotein (AFP) and was negative for MLH-1 and PMS-2, indicating microsatellite instability. This is the first reported case of AFP-negative HME. HME unanimously present in the 6 th decade or later with post-menopausal bleeding and elevated serum AFP. Histologically, hepatoid morphology is most commonly admixed with endometrial adenocarcinoma (56%) or carcinosarcomas (28%), but rare pure hepatoid carcinomas (11%) also occur. Hepatoid differentiation is often found in the myometrium, within vasculature, or lymph node metastases and is often positive for AFP and other hepatoid-markers (HepPar-1, Arginase-1, Glypican-3). Like hepatoid malignancies in other organs, HME have an aggressive clinical course. There was statistically significant (p = 0.046) difference between disease stages, with death from disease occurring in 12% of the stage I/II compared to 75% of the stage III/IV cases. Of those who died of disease, 71% had a survival of one year or less, often from early locoregional recurrence and/or lung metastases. Conclusion: This case series is the largest review of HME to date and summarizes the features common to this rare, but histologically distinct, highly aggressive variant. This highlights the importance of thorough examination of uterine resections for variant histology as it is an important component of prognosis and treatment.